Antiviral Effects and Mechanisms of Active Ingredients in Tea - Xinghai Zhang; Haonan Yu; Panjie Sun; Mengxin Huang; Bo Li (Molecules, 2024)
Viruses play a significant role in human health, as they can cause a wide range of diseases, from mild illnesses to severe and life-threatening conditions. Cellular and animal experiments have demonstrated that the functional components in tea, such as catechins, theaflavins, theanine, and caffeine, exhibit significant inhibitory effects on a diverse array of viruses, including influenza, rotavirus, hepatitis, HPV, and additional types. The inhibition mechanisms may involve blocking virus–host recognition, interfering with viral replication, enhancing host immune responses, and inhibiting viral enzyme activity. This article reviews the research progress on the antiviral effects of tea’s functional components and their related mechanisms, hoping to contribute to future studies in this field.